FREIRE, Maria Martha de Luna. Mulheres, mães e médicos: discurso maternalista no Brasil. - Moreira, Rosimeri (Revista Estudos Feministas, 2010)
FREIRE, Maria Martha de Luna. Mulheres, mães e médicos: discurso maternalista no Brasil.